Electronic Differential System for an Electric Vehicle with Four In-wheel PMSM - Yildirim, Merve; Kurum, Hasan (Ieee, 2020)
In this paper, an Electronic Differential System (EDS) is proposed for an Electric Vehicle (EV) with four In-wheel Permanent Magnet Synchronous Motors (PMSM). EDS is preferred in EVs due to important advantages such as not being mechanical losses caused by the powertrains and hence, reduction of the EV weight. Generally, an EDS design for front or rear wheels of the EV has been handled separately in the literature. On the contrary in this study, an EDS for four wheels of an EV with in-wheel PMSM is realized. There are very little studies on this subject in the literature. According to the speed of the EV and steering angle, the speeds of all wheels are calculated by using the equations derived from Ackermann-Jeantand model. An encoder is used for taking the steering angle via Controller Area Network-Bus (CAN-Bus) and the speed of the EV is obtained by a gas pedal. All speeds of four wheels are calculated by using Codesys Software Package for different the steering angles and the speed values of the EV. Then, the simulation of the EDS is also realized by Matlab/Simulink to verify the Codesys results. It is seen that the proposed EDS is convenient for EVs with four in-wheel PMSMs.
92nd IEEE Vehicular Technology Conference (IEEE VTC-Fall) -- OCT 04-07, 2020 -- ELECTR NETWORK
Keywords: in wheel PMSM; electronic differential system; electric vehicle; Codesys; CAN-Bus communication; vehicular electronics; Matlab/Simulink